Kuliah Kerja Nyata (KKN) Tematik Pemberdayaan Mahasiswa Magang Setjen DPR RI Melalui Edukasi Penggunaan QRIS - Erol Selvio Letwar; Nopha; Kevin Hermanto Tupamahu (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (KKN) is one form of the implementation of the Tri Dharma of Higher Education, particularly in the aspect of community empowerment. Through KKN, students can actively participate in advancing and developing the potential of the community by applying the knowledge and technology they have learned. One of the programs implemented is the education on the use of Quick Response Code Indonesian Standard (QRIS) as a digital payment system. The QRIS socialization program aims to introduce and educate the public on the use of digital payment technology. The socialization activities include direct counseling, workshops, and demonstrations of using QRIS in daily transactions. The implementation of this program involves various communication methods to ensure that the information is well received by different segments of the community. The ongoing socialization activities show that the community is beginning to understand the benefits and convenience offered by QRIS. Besides increasing transaction efficiency, QRIS also helps reduce dependence on cash and expand financial inclusion. This program is expected to be an initial step in creating a more inclusive and efficient digital payment ecosystem in the future.